Use of complementary and integrative medicine among German breast cancer patients: predictors and implications for patient care within the PRAEGNANT study network - Fremd, Carlo; Schneeweiss, Andreas; Rauch, Geraldine; Sohn, Christof; Schütz, Florian; Wallwiener, Markus (Archives of gynecology and obstetrics, 2017)
PurposeThe present study aims to analyze a cohort of advanced breast cancer patients in Germany to assess their interest in complementary and alternative medicine (CAM) and patient’s use of most frequent CAM methods.Patients and methodsBased on the PREGNANT real-time breast cancer registry which is a multicenter study in Germany, questionnaires of 580 patients with advanced breast cancer were evaluated. The implemented questionnaire for CAM asked for general interest in CAM and for patient’s use of different CAM methods at present and in the past. The interest and application of CAM were analyzed for association with patients’ characteristics such as tumor, patient, and therapy characteristics.ResultsIn total, 436 out of 580 (75%) patients claimed to be interested in CAM. Further, interest in CAM is significantly correlated with younger age and absence of metastasis at the time of diagnosis. Multivariate analysis confirmed the patient’s age and distant disease status at the time of diagnosis as related to interest in CAM. A total of 56.4% of patients applied any CAM method in the past. Moreover, with increasing lines of therapies, the more frequent use of CAM was observed. Hereby, praying, vitamin supplements, and other food supplements were most frequently applied.ConclusionOur data demonstrate high overall interest and frequent use of CAM in advanced breast cancer patients supporting a strong demand of breast cancer patients for complementary counseling and treatments additional to the established cancer therapies. It is indispensable to implement counseling and evidence-based complementary treatments into clinical routine of cancer centers and to adapt postgraduate medical education, respectively.
Gesehen am 03.05.2018